2021
DOI: 10.1177/09603271211040819
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic, hemodynamic, and biochemical evidence on the protective effects of exenatide against phosphine-induced cardiotoxicity in rat model

Abstract: Aluminum phosphide (AlP) poisoning can be deadly in most cases targeting the heart. To overcome AlP toxicity, exenatide has been studied in the present study due to its pleiotropic effects on cardiac damages. In this study, the rats were exposed to LD50 of AlP (10 mg/kg) by gavage, and exenatide at doses (0.05, 0.1, and 0.2 mg/kg) injected intraperitoneally 30 min after poisoning. The cardiac parameters including heart rate (HR), blood pressure (BP), QRS, corrected QT (QTc), and ST were monitored for 180 min. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Several studies have shown that cardiovascular disorders are the leading cause of death in the first 12–24 h after phosphine poisoning ( Jafari et al, 2015 ; Asghari et al, 2017 ; Bameri et al, 2021 ). Based on some findings from previous studies, intensive oxidative stress, disturbance of electron transport chain (ETC) in mitochondria, interfering with several macromolecules, and apoptosis are the main mechanisms of AlP poisoning ( Armandeh et al, 2021 ; Hooshangi Shayesteh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that cardiovascular disorders are the leading cause of death in the first 12–24 h after phosphine poisoning ( Jafari et al, 2015 ; Asghari et al, 2017 ; Bameri et al, 2021 ). Based on some findings from previous studies, intensive oxidative stress, disturbance of electron transport chain (ETC) in mitochondria, interfering with several macromolecules, and apoptosis are the main mechanisms of AlP poisoning ( Armandeh et al, 2021 ; Hooshangi Shayesteh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is no specific antidote for managing the cardiac toxicity effects of AlP to date. The protective impacts of several agents such as cannabidiol ( Hooshangi Shayesteh et al, 2022 ), acetyl- l -carnitine ( Baghaei et al, 2016 ), vasopressin ( Jafari et al, 2015 ), melatonin ( Asghari et al, 2017 ), Mg nanoparticle ( Baeeri et al, 2013 ), triiodothyronine ( Abdolghaffari et al, 2015 ), iron sucrose ( Solgi et al, 2015 ), levosimendan ( Armandeh et al, 2021 ; Baeeri et al, 2022 ), taurine ( Samadi et al, 2021 ), exenatide ( Bameri et al, 2021 ), and minocycline ( Haghi-Aminjan et al, 2018 ) on the cardiac toxicity of phosphine have been investigated. However, there is no entirely effective treatment for the management of AlP-cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is a controlled cell death playing a crucial role in maintaining cellular homeostasis ( 56 , 57 ). Any disturbances regulating this pathway lead to cellular abnormalities and diseases ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen 4-week-old male db/db mice were randomly divided into exenatide (n = 8) or control group (n = 8) and maintained in a specific-pathogen free, temperature-controlled environment under 12 h light/dark cycles. Mice in exenatide group received subcutaneous short-acting exenatide (Byetta, Baxter Pharmaceutical Solutions LLC., Indiana, USA) administrations (200 µg/kg body weight) (Bameri et al 2021 ; Tatarkiewicz et al 2013 ). Control mice received an equal volume of saline solution.…”
Section: Methodsmentioning
confidence: 99%